Inhaled corticosteroids do not reduce initial high activity of matrix metalloproteinase (MMP)-9 in exhaled breath condensates of children with asthma exacerbation: a proof of concept study - Grzela, Katarzyna (Cent Eur J Immunol, 2016)
Inhaled corticosteroids (ICS) are the key component of asthma treatment. However, it is unclear whether they could control the activity and level of matrix metalloproteinase (MMP)-9, which is an important factor in asthma-associated inflammation and airway remodeling. Therefore, the aim of this proof of concept study was to analyze the influence of increased doses of ICS on MMP-9 in exhaled breath condensates (EBC) of patients with allergic asthma exacerbation. Apart from MMP-9, the assessment concerned selected inflammation markers – exhaled nitric oxide (eNO) and cytokines (IL-8 and TNF). The study involved a small group (n = 4) of individuals with asthma exacerbation. The intervention concerned increased doses of ICS with β-mimetics for 4 weeks. In addition to clinical evaluation, eNO measurements and EBC collections were done before and after 4 weeks of intense ICS treatment. The biochemical assessment of EBC concerned MMP-9, IL-8 and TNF. The data were compared to results of healthy controls (n = 6). The initial levels of eNO, MMP-9 and TNF in EBC were higher in the asthma group than in controls. In all subjects IL-8 levels were below the detection limit. After 4 weeks of ICS treatment in all patients we observed improvement of clinical and laboratory parameters. Interestingly, despite reduction of eNO and TNF, the activity of MMP-9/EBC remained on the initial level. Practical relevance of our results is limited by a small group. Nevertheless, our data suggest that ICS, although sufficient to control symptoms and inflammatory markers, may be ineffective to reduce MMP-9/EBC activity in asthma exacerbation and, possibly, airway remodeling.